Analisis Kesulitan Menghafal Surah Pendek Siswa Kelas IV - Qomariah, Annisa; Adianto, Samsul; Arpiani, Tini; Fitriyani, Rini (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2024)
This study aims to determine the results of an analysis of the difficulty of memorizing short surahs during online learning for fourth grade students. Data analysis was carried out in the following stages, namely data reduction, data presentation and drawing conclusions, then testing the validity of the data through source triangulation. The research results show that the difficulty in memorizing short surahs, namely Al-Humazah and At-Takasur during online learning, is due to several factors, including students who cannot recite the Koran well or are not fluent in reciting the Koran, often forgetting memorized verses, feeling lazy, health problems and lack of attention from parents/guardians of students. Thus, it can be concluded that there are many factors that cause fourth grade students to experience difficulty memorizing short surahs during online learning, but teachers and parents also make efforts to overcome difficulties in memorizing short surahs, including by always reminding students to memorize them, providing encouragement and encouragement. as well as helping students at home if they have difficulty memorizing short surahs.